Deep-Drawing and Fatigue Properties of Advanced Steel Sheet Stripes - Bursak, Marian; Michel, Jan (Communications - Scientific letters of the University of Zilina, 2010)
Analysis of the deep drawing and fatigue properties is given in this contribution for two advanced micro alloyed sheet steel grades with Yield strength values Re 246 and 382 MPa, respectively. The 2 mm thick steel sheets were hot dip zinc coated. The deep drawing properties were evaluated by tensile testing and by the Erichsen test at different strain rates. For fatigue testing the symmetric bending test was applied. Results showed favorable deep drawing properties of these steel sheets assigned for heavy duty parts in automotive industry. Steel grade with Re 246 MPa had elongation A80 32%, n 0.21, Erichsen number IE 12.5 mm and the steel with Re 382 MPa had A80 24 %, n 0.17 and IE 12.4 mm. The tested values showed some growth in dependence on the strain rate up to the press tool velocity about 0.1 m.s1 and at higher strain rates they decreased. The fatigue limit in bending was about 0.6.Re . The zinc coating on the sheet surface remains complete up to the final fracture of the test piece.